2021
DOI: 10.3389/fphar.2021.802381
|View full text |Cite
|
Sign up to set email alerts
|

Xiaoxuming Decoction: A Traditional Herbal Recipe for Stroke With Emerging Therapeutic Mechanisms

Abstract: Xiaoxuming decoction (XXMD) has been traditionally used to manage stroke though debates on its clinical efficacy were present in the history. Till nowadays, it is still one of the most commonly used herbal recipes for stroke. One of the reasons is that a decent proportion of ischemic stroke patients still have residue symptoms even after thrombolysis with rt-PA or endovascular thrombectomy. Numerous clinical studies have shown that XXMD is an effective alternative therapy not only at the acute stage, but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…For example, children are usually advised to take a half of the dose, and the patient whose condition improves very well is usually advised to appropriately take less dose of XXMD. However, we did not find the detailed reports which studied that the heavier patients should get larger doses, and neither found the detail reports which showed the relationship between the patients' condition and the doses of XXMD the patients should get, while the clinical applications are sometimes mentioned in some literatures (Zhang et al, 2021). Even though there are not enough randomized controlled trials to clearly prove and judge the user population in most of the current studies, XXMD has been listed in the first batch of classic prescriptions in China (Cai et al, 2007;Fu et al, 2013;Luo X. et al, 2019;Jia et al, 2019) and is still to be recommended with its effectiveness and safety, which is consistent with the views of some researchers (Fu et al, 2013;Fu and Cai, 2016;Chen Q. R. et al, 2017;Jiang and Li, 2020;Huang et al, 2021).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…For example, children are usually advised to take a half of the dose, and the patient whose condition improves very well is usually advised to appropriately take less dose of XXMD. However, we did not find the detailed reports which studied that the heavier patients should get larger doses, and neither found the detail reports which showed the relationship between the patients' condition and the doses of XXMD the patients should get, while the clinical applications are sometimes mentioned in some literatures (Zhang et al, 2021). Even though there are not enough randomized controlled trials to clearly prove and judge the user population in most of the current studies, XXMD has been listed in the first batch of classic prescriptions in China (Cai et al, 2007;Fu et al, 2013;Luo X. et al, 2019;Jia et al, 2019) and is still to be recommended with its effectiveness and safety, which is consistent with the views of some researchers (Fu et al, 2013;Fu and Cai, 2016;Chen Q. R. et al, 2017;Jiang and Li, 2020;Huang et al, 2021).…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, ischemic stroke has 14 similar pathogenetic genes, ACVRL1, APP, ABCC6, CST3, ENG, F7, JAK2, PLAT, PLAU, VHL, SH2B3, PDCD10, KIF1B, and CCM2, and has 48 similar signaling pathways to hemorrhagic stroke, whereas the stroke-related ID C0553692 is related to hemorrhagic stroke and to 29 pathogenetic genes and 48 signaling pathways. It indicated that ischemic stroke and hemorrhagic stroke are both important in the study of XXMD (Zhang et al, 2021). In addition, most of the top 30 GO terms of pathogenetic genes are closely associated with stroke, such as response to oxidative stress (GO:0006979) (Chen et al, 2020;Zhang et al, 2020d) and regulation of inflammatory response (GO:0050727) (Zhang et al, 2014;Xu S. et al, 2020).…”
Section: Identification Of Pathogenetic Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke was categorized as acute cerebrovascular disease in modern medicine. 1 Risk factors such as population aging, diet change, and work pressure lead to an average annual increase of 8.3% in the incidence rate of stroke. 2,3 Studies have shown that about 70% of patients have motor dysfunction after stroke, and 14% to 71% have swallowing dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, AI techniques have recently been utilized to develop a prescription decision supporting system using traditional contexts or explore the efficacy of herbal extracts and prescriptions (Han et al, 2018;He et al, 2019;Zhou et al, 2021). For instance, numerous research studies were conducted to scrutinize neuroprotective compounds via machine learning methods from Xiaoxuming decoction, which affects regulating vascular function and treating stroke recovery (Fu et al, 2013;Shen et al, 2021;Yang et al, 2019;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%